Clinical and Experimental Insights into Hydroxychloroquine-Associated Electrical Abnormalities and Cardiomyopathy - Mikio Shiba; Zhaoyang Liu; Shuichiro Higo; Junjun Li; Yoshihiko Ikeda; Lifu Sun; Yuting Liu; Yuki Hara; Shinji Higa; Tatsuya Nishikawa; Yuki Matsuoka; Yu Morishita; et al. (European Heart Journal - Cardiovascular Pharmacotherapy, 2026)
Abstract Aims Hydroxychloroquine (HCQ) is commonly prescribed for malaria and autoimmune diseases, yet its potential for cardiotoxicity remains underrecognised. The objective of this study was to investigate the clinical and experimental features of HCQ-associated cardiotoxicity. Methods and Results We retrospectively analysed 261 HCQ-treated patients, assessing cardiac adverse events and electrocardiographic intervals. Endomyocardial biopsy specimens were examined via transmission electron microscopy. To explore potential pathophysiological correlates, human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) were exposed to HCQ, and electrophysiological, ultrastructural, contractile and autophagy-related responses were evaluated. HCQ was discontinued in 14 patients, including 3 patients with clinically significant cardiotoxicity manifesting as heart failure or an isolated conduction abnormality (1.1% of the cohort). QTc intervals increased from a median of 413 ms (interquartile range [IQR], 399–426 ms) pre-treatment to 421 ms (IQR, 407–440 ms) on-treatment (P = 0.003), indicating a modest but statistically significant change. PR interval also increased modestly from 148 ms (IQR, 140–163 ms) to 150 ms (IQR, 142–168 ms) (P = 0.041). In vitro, HCQ exposure in hiPSC-CMs prolonged corrected field potential duration (P = 0.013) and induced arrhythmic activity. Motion analysis demonstrated a reduced peak relaxation velocity (P < 0.01), with concomitant attenuation of contractile function. Transmission electron microscopy showed lamellar inclusions consistent with myelin-like bodies. HCQ exposure significantly increased autophagy-related protein levels, suggesting impaired autophagic degradation. These cellular phenotypes closely mirrored clinical manifestations of HCQ-associated electrical abnormalities and cardiomyopathy. Conclusion HCQ therapy is associated with electrical abnormalities and cardiomyopathy. Experimental findings in hiPSC-CMs recapitulate key clinical features, providing biologically supportive evidence.